BRIDGING EDUCATION AND WORK: BENEFITS AND CHALLENGES OF ONLINE LEARNING FOR WORKING STUDENTS - Herlyna Herlyna (STKIP PGRI Situbondo, 2025)
To keep ahead in the highly competitive employment market of today, working professionals need to constantly improve their skills. One effective way to accomplish this is by pursuing higher education. This study explores both the benefits and challenges faced by working students who are enrolled in online college courses. Using a descriptive qualitative approach, the researcher examines insights from 15 participants, attending online classes in Pertiwi University, Jakarta. Data was collected through a combination of questionnaires, as well as students' scores and attendance records. These data were analyzed to identify key insights regarding the benefits and challenges experienced by students in an online learning environment. The results provide valuable understanding of the benefits and challenges that these students experience while pursuing their education online. The online learning offers significant advantages, such as ease of access; however, the online learning also has disadvantages, such as the limited interactions with peers and lecturers. Based on these findings, the study recommends further research to explore the relationship between students’ perceptions of online learning and their academic performance, as well as to investigate strategies that can be implemented by the institutions to better support the students in the online learning setting.